THE INFLUENCE OF CHINESE TRADITIONAL CULTURE ON THE CULTIVATION OF POSITIVE PSYCHOLOGICAL QUALITY AND CHARACTER HEALING OF COLLEGE STUDENTS - Zichun Zhao; Wei Wang; Juan Hao (Fonseca, Journal of Communication, 2024)
The views, attitudes, and psyches of Chinese people are heavily influenced by traditional culture. We need to understand the influence of culture on people’s psychology and behavior as well as the link between psychological quality and character healing in China. Traditional Chinese philosophy is at the heart of Chinese culture, and examining the inner human existence afforded by traditional Chinese concepts is essential. Some modern college students are conflicted about their political convictions, ambiguity regarding their values and beliefs, lack of honesty and trustworthiness, lack of social duty, and poor psychological health. Traditional culture may help psychological inadaptability by resisting the setbacks of detachment and tolerance. Exploring the positive impact of Chinese formal culture education on college students may assist in relieving and promoting psychological quality and character healing in college students. The participants were 564 university students from nine departments at a public university in Macau, China, SAR. The students were randomly divided into two groups: one as the control group, which provided conventional education, and the other as the study group, which set up a course on traditional Chinese culture. Students’ performance was assessed using a student t-test, Cronbach’s alpha, and the panel unit root test. Finally, the proposed approach is examined and compared with existing methods. Before the experiment, no significant differences were observed between the two groups. Still, after the investigation, the experimental group’s psychological quality and character healing were better than before the experiment. Integrating traditional Chinese culture into a college education and personality development can help develop and improve the psychological qualities and characteristics of college students.